Investment Inefficiency and Financial Distress: Evidence from ASEAN Non-Financial Firms - Mochammad Rifni; Isnalita Isnalita (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the effects of investment intensity, over-investment, and under-investment on financial distress among non-financial firms in ASEAN. The study aims to investigate whether inefficient investment behavior increases firms’ financial vulnerability. Research Method: This study employs unbalanced panel data obtained from the Bureau van Dijk OSIRIS database covering the 2020–2024 period, with a total of 14.371 firm-year observations. Financial distress is measured using the Altman Z”-Score model, while investment inefficiency is proxied by over-investment and under-investment. The analysis applies the fixed effects model with robust standard errors clustered at the firm level. In addition, robustness tests are conducted using ordinary least squares (OLS) and the random effects model (REM). Results and Discussion: The findings indicate that investment intensity and over-investment significantly increase financial distress risk, suggesting that inefficient investment allocation may weaken firms’ financial conditions. Meanwhile, under-investment does not show a significant effect on financial distress. The robustness test results remain consistent across alternative estimation models, confirming the reliability of the findings. Implications: This study provides implications for managers and investors regarding the importance of efficient investment decisions in maintaining firms’ financial stability. Future studies are expected to employ broader databases and additional variables to capture firms’ investment behavior more comprehensively. Originality: This study contributes to the literature by examining the relationship between investment inefficiency and financial distress in the ASEAN context using recent panel data evidence.